Nanoemulsions and Their Potential Applications in Food Industry - Aswathanarayan, Jamuna Bai; Vittal, Ravishankar Rai (Frontiers in Sustainable Food Systems, 2019)
Nanoemulsions have small droplet size and are kinetically stable colloidal systems. They have enhanced functional properties in comparison to conventional emulsions. The composition and structure of the nanoemulsions can be controlled for the encapsulation and effective delivery of bioactive lipophilic compounds. Nanoemulsions have potential application in the food industry for the delivery of nutraceuticals, coloring and flavoring agents, and antimicrobials. The nanoemulsion formulations of active ingredients can be used for developing biodegradable coating and packaging films to enhance the quality, functional properties, nutritional value and shelf life of foods. This review focuses on preparation of food grade nanoemulsions using high-energy methods and low-energy approaches and their characterization for physical properties, stability and microstructure. The application of nanoemulsion formulations for sustainable food processing and improving the delivery of functional compounds, such as colorants, flavouring agents, nutraceuticals and preservatives or antimicrobial agents in foods has been discussed.